Launch of theFood Security Simulator – Nigeria (Presentation) - Ecker, Olivier (CGIAR System Organization, 2023)
These slides were presented by Olivier Ecker at the Launch of the Food Security Simulator Nigeria last Oct. 31, 2023 at Abuja Nigeria. The Food Security Simulator – Nigeria was developed by the International Food Policy Research Institute (IFPRI), under the CGIAR Research Initiative on National Policies and Strategies (NPS), with important contributions from National Bureau of Statistics (NBS), Federal Ministry of Agriculture and Food Security (FMAFS), Federal Ministry of Humanitarian Affairs, and Poverty Alleviation Reduction (FMHAPA), and other partners in Nigeria during the validation processes of the tool. This work was made possible by support from the CGIAR Trust Fund.